Les Offices du cinéma scolaire et éducateur à l’épreuve des publics - Pascal Laborderie (Conserveries Mémorielles)
In France, between the two World Wars, the Educational Cinema Offices built a network of teaching, education and propaganda using cinema. How can the effects of this network be assessed? First of all, we examine the plans of action implemented by the Educational Cinema Offices as an answer to the multiplicity of the audiences, children and adults, men or women, working and middle classes, from rural or urban places, from mainland France or colonies. Then the interest of cinema as a matter of teaching in front of children is considered from speeches of teachers. Finally, this article tackles the opinion of the teachers on the propaganda for adults. From speeches to reality, we suggest that this propaganda especially made the driving forces of the Offices work together when the various movements of the centre and of the left wings were divided.